Comparative study of anaphylaxis incidence in patients receiving anti-snake venom with or without prophylactic adrenaline: a prospective, randomized, blinded study - S., Raghuraman M.; B., Sivaraman (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Anti-snake venom serum (ASV) administered for snake-bite patients is the most specific treatment available. Unfortunately, it can cause severe anaphylaxis which can be fatal sometimes. Methods: Fifty patients were included in the study and randomly divided into group A, who received sub-cutaneous adrenaline before administration of anti-venom serum and group B who did not. Each group comprised of twenty-five patients. The incidences as well as the severity of anaphylaxis in both groups and also the effects of subcutaneous adrenaline on the hemodynamic were analysed. Results: Anaphylactic reactions were significantly less in group A than group B population (p<0.05). Hemodynamic variables such as blood pressure, pulse rate have responded similarly in both the groups (p>0.05) implying that administration of sub-cutaneous adrenaline is safe. Conclusions: Prophylactic subcutaneous adrenaline before anti snake venom administration is highly efficacious and safe in reducing the incidence as well as severity of anaphylactic reactions.